Claudio Moraga : a passion for multi-valued logic and soft computing - Seising, Rudolf, 1961-; Allende-Cid, Héctor; Moraga, Claudio (Studies in fuzziness and soft computing ;, 2016)
The book is an authoritative collection of contributions by leading experts on the topics of fuzzy logic, multi-valued logic and neural network. Originally written as an homage to Claudio Moraga, seen by his colleagues as an example of concentration, discipline and passion for science, the book also represents a timely reference guide for advance students and researchers in the field of soft computing, and multiple-valued logic. .